Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan: Studi Kasus Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2016-2020 - Manurung, Tarida Marlin Surya; Wildan, Muhammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to examine various relationships between hypothetical variables. The variables used in this study are capital structure, which is proxied by the debt- to -equity ratio (DER), firm size, which is proxied by total assets, and firm value, which is proxied by the price earnings ratio (PER). This study aims to determine the effect of capital structure and firm size on firm value partially and simultaneously on foods and beverages listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Samples were taken using purposive sampling method. The population in this study are all industrial companies in the food and beverage sector that have been and are still listed on the Indonesian Stock Exchange for the 2016-2020 period. Out of the 26 population, companies obtained 7 companies that meet the requirements as a sample during the 5 year observation period. Statistical methods used in data processing and analysis are normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, and hypothesis testing with t test and f test. The results showed that the capital structure (X1) had a significant effect on firm value. Firm size (X2) has a significant effect on firm value. Capital structure (X1) and firm size (X2) indicate that they simultaneously affect firm value.